Quantitative precipitation reconstructions from Chagan Nur revealed lag response of East Asian summer monsoon precipitation to summer insolation during the Holocene in arid northern China. (1st July 2020) - Li, Guoqiang; Wang, Zhong; Zhao, Wenwei; Jin, Ming; Wang, Xiaoyan; Tao, Shuxian; Chen, Chunzhu; Cao, Xianyong; Zhang, Yunian; Yang, He; Madsen, David
Abstract: East Asian summer monsoon (EASM) variability is primarily responsible for climate change in East Asia, influencing over a billion lives. The pattern and mechanisms of EASM change during the Holocene are intensely debated. In this study, we produce a high-quality age-depth model for a 11.7 m lacustrine record (CG18B core) from central Chagan Nur (a closed-basin lake located on the southern Mongolia plateau at the fringe of the modern EASM region) using 27 radiocarbon dates on organic materials and 10 quartz optically stimulated luminescence (OSL) ages on the lake sediments. Multiple-proxy analyses of pollen, grain size, total organic content, and CaCO3 content are used to reconstruct Holocene monsoonal precipitation change in the region. Reconstructed Chagan Nur level changes during the Holocene are based on 18 quartz OSL ages from well-preserved paleolake shorelines at different elevations on the northwestern basin margin. A combination of the lacustrine pollen records and a paleohydrology lake level change model is used to define quantitative precipitation change at the fringe of the EASM dominated region during the Holocene. Our results show that a lake highstand of 15-12 m higher than present occurred at 11–5 ka, followed by a decrease in lake levels to 8-7 m higher than present at 4–3 ka, and a general lake lowering during the late Holocene. EASM dominated annual precipitation varied between 420 mm and 280 mm during the Holocene period in the basin, indicating a generally semi-arid environment on the southern Mongolian Plateau, and corresponding to prevailing open steppe vegetation in the basin throughout the Holocene. EASM precipitation intensity increased from the early Holocene to the beginning of the mid-Holocene, with a maximum precipitation 30–50% higher than present at 8–6 ka, followed by a decrease in precipitation during the late Holocene. EASM precipitation shown in these records lags northern Hemisphere solar insolation shifts by ∼3 ka, indicating that variation in EASM intensity did not respond directly to northern Hemisphere summer insolation, but rather was likely modulated by high latitude forcing of ice volume and greenhouse gases. Highlights: Precipitation is quantitatively calculated using lake pollen and lake level records. Lake high stands occurred at 11-5 ka, followed by a decreasing trend after 5 ka. Precipitation varied between 420-280 mm/yr during the Holocene at modern ASM fringes. ASM precipitation was a maximum of 30-50 % higher than present at 8-6 ka. ASM intensities have a ∼3 ka lagged response to 30 °N summer insolation.